Hyperthyroidism Symptoms, Management, and Outcomes in Children and Adults Seeking Definitive Surgical Treatment. Issue 5 (May 2021) - Chung, Sebastian K.; Asban, Ammar; Hur, Jinwoo; Iyer, Pallavi; Chen, Herbert
Abstract : Objective: To identify the difference in presentation, time to treatment, and outcomes between hyperthyroid adults and children referred to surgical evaluation. Background: There is little data on differences in presenting symptoms, time to treatment, and outcomes between adults and children presenting for thyroidectomy for Graves' disease. Methods: We retrospectively reviewed records of patients with hyperthyroidism referred for thyroidectomy between January 2016 and April 2017. We divided our cohort into 2 groups based on age, children (age ⩽18 years), and adults (age >18), and evaluated the difference in prevalence of symptoms, time from diagnosis, and initiation of antithyroid medications to surgery, and outcomes. Results: We identified 38 patients (27 adults and 11 children) with data on hyperthyroidism symptoms referred for thyroidectomy. Relative to hyperthyroid adults, children with hyperthyroidism were more likely to present with hoarseness (55% vs 15%, P = 0.01) and difficulty concentrating (45% vs 7%, P = 0.01) at initial presentation. There was no statistically significant difference in prevalence of vision changes, exophthalmos, pretibial myxedema, palpitations, fatigue, temperature intolerance, dysphagia, tremors, or constitutional symptoms. A median of 15 months elapsed from diagnosis to thyroidectomy among adult and 6 months among pediatric patients. Adult and pediatric patients waited a median of 13 and 6 months from initiation of antithyroid medications to thyroidectomy, respectively. There was no significant difference in outcomes. Conclusions: Children with hyperthyroidism were more likely to present with hoarseness and difficulty concentrating than adults. Concentration and communication are critical skills in developing children, and early intervention with definitive therapy may improve such symptoms. Abstract : Supplemental Digital Content is available in the text